Demystifying Cancer Immunotherapy for Lay Audiences - Ellis, Kiara; Pennell, Christopher A. (Frontiers in Immunology, 2019)
Immunotherapy is now mainstream. Advertisements are ubiquitous in print and visual media for immune based-therapies for various conditions and diseases. Smaller companies that develop novel immunotherapies are often quickly acquired by larger companies. More and more clinical trials are open for immune-based therapies, particularly for immune checkpoint blockades. As such, immunologists need to engage the public in conversations about the strengths and limitations of immunotherapy, and the necessity of research in propelling the field further. In this article, we discuss approaches we have taken to convey key concepts in immunology and cancer immunotherapy to non-scientists and health care professionals without expertise in immunology. Although the devil is always in the details, basic concepts in immunology and immunotherapy can be readily conveyed using stories and analogies, some of which we present here.